(untitled) (Journal of Preventive and Social Medicine, 2023)
Background: Cost of treatment is a major concern in Bangladesh, as well as in many other lower- and middleincome countries and more than half of treatment cost is beard by the patient’s family which is out-of-pocket expenditures. The casualty unit of a hospital is the ultimate place for moderate to severely injured patients. Methods: A hospital-based cross-sectional study was commenced to estimate the out-of-pocket expenditures (OPE) incurred by the injured patients among 140 admitted injured patients. Data were collected by face-to-face interview through a pretested semi-structured questionnaire. Results: The mean age was 33.3±12.8 years and most of the patients (46.0%) resided in urban areas. The mean monthly family income was 26242.9±12698.9 taka. The majority of the patients had a single wound (71.4%), which was simple hurt (78.6%) in grading. The mean of the total direct costs was 8,936.5±9,437.7 taka and the mean of the total indirect cost was 2,057.0±3,189.9 taka. The mean of total OPE was 10,993.5±11,126.9 taka. Patient’s sex, residence and their grade of injuries (p<0.05) were statistically significant with total OPE by the patients. Conclusion: This study provided some insight into the OPE in the casualty unit of CMCH. Proper referral system and implementation of health insurance can reduce the OPE burden. This study might help developing strategies in hospital settings. JOPSOM 2021; 41(1):35-40